Examining the signs and symptoms experienced by individuals with suspected acute coronary syndrome in the Asia-pacific region: A prospective observational study - Greenslade, J.; Cullen, L.; Parsonage, W.; Reid, Christopher; Body, R.; Richards, M.; Hawkins, T.; Lim, S.; Than, M. (2012)
Study objective: This study examines whether symptoms reported by patients presenting with possible acute coronary syndrome vary across different ethnic backgrounds. We also assess the predictive value of individual symptoms according to ethnic background. Methods: The study used prospectively collected data on adult patients presenting with suspected acute coronary syndrome to 12 emergency departments in the Asia-Pacific region. Trained research nurses collected data on ethnicity, type of pain, and associated symptoms, using a customized case report form. The primary endpoint was acute coronary syndrome within 30 days of presentation, as adjudicated by cardiologists using standardized guidelines. Logistic regression analyses assessed the relationship between ethnicity and symptom type and the predictive value of symptom type for acute coronary syndrome. Results: Acute coronary syndrome was diagnosed in 358 (19.2%) of the 1,868 patients recruited. In comparison with white patients, Chinese patients were less likely to report atypical pain (odds ratio [OR]=0.26; 95% confidence interval [CI] 0.2 to 0.34), exertional pain (OR=0.41; 95% CI 0.32 to 0.53), pleuritic pain (OR=0.26; 95% CI 0.19 to 0.35), pain on palpation (OR=0.31; 95% CI 0.2 to 0.49), nausea (OR=0.52; 95% CI 0.42 to 0.67), diaphoresis (OR=0.41; 95% CI 0.33 to 0.51), and shortness of breath (OR=0.59; 95% CI 0.48 to 0.73). The comparison of white with other ethnic groups yielded similar results. The predictive value of symptoms was similarly poor across different ethnic groups, with the notable exception of India, where typical pain was predictive of acute coronary syndrome (OR 8.82; 95% CI 2.19 to 35.48). Conclusion: There are cross-cultural differences in symptoms reported by patients with suspected acute coronary syndrome. Such differences are not likely to be clinically relevant because the majority of symptoms display limited diagnostic value for acute coronary syndrome. Copyright © 2012 by the American College of Emergency Physicians.